Economic and Environmental Benefits of Grid-Connected PV-Biomass Systems in a Bangladeshi University: A HOMER Pro Approach - Md. Feroz Ali; Md. Abdul Halim; Mir Md. Julhash; Md Ashikuzzaman (International Transactions on Electrical Energy Systems)
This study addresses Bangladesh’s urgent power crisis by evaluating a grid-connected PV-Biomass hybrid system at the Pabna University of Science and Technology (PUST). Using the hybrid optimization of multiple energy resources (HOMER) software, the project showcases a cost-effective and environmentally friendly solution. The system achieves a cost of energy (COE) of $0.0347/kWh and a net present cost (NPC) of $4,712,218, with annual operating costs of $95,679.09. It significantly reduces carbon dioxide emissions from 1,920,065 kg/yr to 839,600 kg/yr and offers a competitive payback period of 6.52 years. These results highlight the system’s economic viability and environmental advantages, proposing a scalable model for similar institutions in developing countries striving for sustainable energy solutions. This approach not only mitigates the current energy challenges but also aligns with global sustainability goals.